2021
DOI: 10.1111/iep.12388
|View full text |Cite
|
Sign up to set email alerts
|

Protein restriction during puberty alters nutritional parameters and affects ovarian and uterine histomorphometry in adulthood in rats

Abstract: Nutritional status in prenatal and early postnatal life plays a critical role in the development and homeostasis of the organism. Early malnutrition seems to alter the original programming of the organs, especially those dependent on specific developmental stages, which may result in long-term metabolic changes. 1,2 Proteins are substances found in higher amounts in the body, constituting approximately 10%-20% of the cell mass. Their actions are divided between structural components such as the formation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…36 Mice with PD caused by consuming feed with a 6% protein content had a higher energy intake, thereby increasing the total fat weight and reducing lean body mass compared to normal mice consuming 20% protein. 37,38 A lack of protein intake causes increased hunger, resulting in a tendency to consume large amounts of food. Such occurs because proteins can create a longer-lasting feeling of fullness than carbohydrates and fats.…”
Section: Discussionmentioning
confidence: 99%
“…36 Mice with PD caused by consuming feed with a 6% protein content had a higher energy intake, thereby increasing the total fat weight and reducing lean body mass compared to normal mice consuming 20% protein. 37,38 A lack of protein intake causes increased hunger, resulting in a tendency to consume large amounts of food. Such occurs because proteins can create a longer-lasting feeling of fullness than carbohydrates and fats.…”
Section: Discussionmentioning
confidence: 99%
“…In order to address this gap, we will compile and synthesise existing relevant studies in rodents to exemplify this aspect. In rats, nutritional protein restriction during puberty increased the oestrus phase arrest without changing the length of the oestrus cycle in adult females 20 . In addition, the low‐protein diet reduced the level of androgen receptor and elevated the oestrus receptor β in ovaries of rats 20 .…”
Section: Undernutrition and Human Reproductionmentioning
confidence: 98%
“…In rats, nutritional protein restriction during puberty increased the oestrus phase arrest without changing the length of the oestrus cycle in adult females. 20 In addition, the low-protein diet reduced the level of androgen receptor and elevated the oestrus receptor β in ovaries of rats. 20 Another study in rats showed that postnatal undernutrition delayed puberty onset.…”
Section: Postnatal/pubertal Undernutrition and Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, as far as we known, there are no reports on the endothelial outcomes of protein restriction during the peripubertal period. The literature shows that protein restriction during puberty can cause metabolic 12,13 and reproductive 12,14 disorders in rats, demonstrating the importance of an adequate diet in the peripubertal period to homeostasis in adult life. In fact, it was recently described that protein restriction during peripubertal period can cause hypertension in adulthood, 15 however, as far as we know, the vascular function was not evaluated in this model.…”
Section: Introductionmentioning
confidence: 99%